Critical Assessment of Protein Cross-Linking and Molecular Docking: An Updated Model for the Interaction Between Photosystem II and Psb27 - Cormann, Kai U.; Möller, Madeline; Nowaczyk, Marc M. (Frontiers in Plant Science, 2016)
Photosystem II (PSII) is a large membrane-protein complex composed of about 20 subunits and various cofactors, which mediates the light-driven oxidation of water and reduction of plastoquinone, and is part of the photosynthetic electron transfer chain that is localized in the thylakoid membrane of cyanobacteria, algae and plants. The stepwise assembly of PSII is guided and facilitated by numerous auxiliary proteins that play specific roles in this spatiotemporal process. Psb27, a small protein localized in the thylakoid lumen, appears to associate with an intermediate PSII complex that is involved in assembly of the Mn4CaO5 cluster. Its precise binding position on the PSII intermediate remains elusive, as previous approaches to the localization of Psb27 on PSII have yielded contradictory results. This was our motivation for a critical assessment of previously used methods and the development of an improved analysis pipeline. The combination of chemical cross-linking and mass spectrometry (CX-MS) with isotope-coded cross-linkers was refined and validated with reference to the PSII crystal structure. Psb27 was localized on the PSII surface adjacent to the large lumenal domain of CP43 on the basis of a cross-link connecting Psb27-K91 to CP43-K381. Additional contacts associating Psb27 with CP47 and the C-termini of D1 and D2 were detected by surface plasmon resonance (SPR) spectroscopy. This information was used to model the binding of Psb27 to the PSII surface in a region that is occupied by PsbV in the mature complex.